(N{UM WREMENI(B: [(No^ERKI(B]; s (NpEREWODY (B/ s (N~ASTX (B2s - (NmANDELX[TAM(B, (NoSIPs ((NmOSKWA(B: s (NhUDOVESTWENNAQ LITERATURA(B, s, 1990)
(NwO WTOROJ TOM sO^INENIJ o(B. (N|(B. (NmANDELX[TAMA WO[LI EGO LU^[IE PROZAI^ESKIE PROIZWEDENIQ (B- (NAWTOBIOGRAFI^ESKAQ PROZA I O^ERKI(B, (NIZBRANNYE STATXI I \SSE PO ISTORII MIROWOJ KULXTURY I PO\ZII(B.s
rus
Keywords: (No^ERKI(B, (N\SSEs; (NpROZAs -- (NsTATXIs